Craniocervical junction diseases treatment with a minimally invasive approach - Díaz,Roberto Carlos (2014)
Objective: To introduce a new minimally invasive surgical approach to anterior and lateral craniocervical junction diseases, preserving the midline posterior cervical spine stabilizing elements and reducing the inherent morbidity risk associated with traditional approaches. Methods: We describe a novel surgical technique in four cases of extra-medullary anterolateral compressive lesions located in the occipito-cervical junction, including infections and intra- and/or extradural tumor lesions. We used a paramedian trasmuscular approach through an anatomical muscle corridor using a micro MaXcess(r) surgical expandable retractor, with the purpose of reducing morbidity and preserving the posterior muscle and ligamentous tension band. Results: This type of surgical approach provides adequate visualization and microsurgical resection of lesions and reduces muscle manipulation and devascularisation, preserving the tension of the ligament complex. There was minimal blood loss and a decrease in postoperative pain, with rapid start of rehabilitation and shorter hospitalization times. There were no intraoperative complications, and all patients recovered from their pre-operative symptoms. Conclusions: This novel surgical technique is feasible and adequate for the occipito-atlanto-axial complex, with better results than traditional procedures.